2010
DOI: 10.1158/0008-5472.can-10-1118
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contextual Responses of Normal Human Breast Epithelium to Ionizing Radiation in a Mouse Xenograft Model

Abstract: Radiotherapy is a key treatment option for breast cancer, yet the molecular responses of normal human breast epithelial cells to ionizing radiation are unclear. A murine subcutaneous xenograft model was developed in which nonneoplastic human breast tissue was maintained with the preservation of normal tissue architecture, allowing us to study for the first time the radiation response of normal human breast tissue in situ. Ionizing radiation induced dose-dependent p53 stabilization and p53 phosphorylation, toge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
(56 reference statements)
2
19
0
1
Order By: Relevance
“…Moreover, the results suggest that p53 response of epithelial cells in their tissue context differs from what is seen in proliferating cell cultures. Interestingly, similar results of attenuated p53 response after IR have been described in primary human breast epithelial cells and ex vivo cultured breast tissues (Coates et al., 2010; Huper and Marks, 2007; Meyer et al., 1999). In fibroblasts the response pattern is reversed: p53 is stabilized and transcriptionally active in cell culture, but compared to the epithelium, the stromal responses in ex vivo ‐cultures are minimal (Coates et al., 2010; Jäämaa et al., 2010, 2012; Zhang et al., 2011).…”
Section: Could Differences In Dna Damage Response Explain Why Prostatsupporting
confidence: 78%
“…Moreover, the results suggest that p53 response of epithelial cells in their tissue context differs from what is seen in proliferating cell cultures. Interestingly, similar results of attenuated p53 response after IR have been described in primary human breast epithelial cells and ex vivo cultured breast tissues (Coates et al., 2010; Huper and Marks, 2007; Meyer et al., 1999). In fibroblasts the response pattern is reversed: p53 is stabilized and transcriptionally active in cell culture, but compared to the epithelium, the stromal responses in ex vivo ‐cultures are minimal (Coates et al., 2010; Jäämaa et al., 2010, 2012; Zhang et al., 2011).…”
Section: Could Differences In Dna Damage Response Explain Why Prostatsupporting
confidence: 78%
“…2325 Coates et al engrafted breast tissue in the sub-cutaneous site of mice, enabling studies of the radiation responses of normal human breast tissue in situ. 26 However, most studies of DDR have been done in proliferating in vitro cell lines and the results of these experimental models may not always reflect situations in vivo. For example, Barreto-Andrade et al reported that radiosensitization by a PARP inhibitor in vitro failed to predict comparable results in tumors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The γ-H2AX signal protein can be visualized within seconds of initiation of a DSB and persists until repair is complete—for typical cells, approximately 24 to 48 hours. Other proteins (the effectors) are also present within minutes of detection of a DSB, including P53 binding protein 53BP1, and either guide the cell toward repair or ultimately force apoptosis by stimulating release of mitochondrial cytochrome c and subsequent activation of caspase-3 [16]. DSBs are the most difficult lesion for a cell to accurately repair and can lead to mutations such as deletions and insertions.…”
Section: Cellular Response To Dna Damagementioning
confidence: 99%